Content Validity of English Summative Test - Rizky Hilaldy (Journal of Language Learning and Research (JOLLAR), 2021)
The objective of the research was to answer the question of the study whether the content of the English summative test of the tenth grade students at SMA An- Nurmaniyah in the 2016/2017 academic year was in line with the English syllabus content of 2013 Curriculum. In this research, the writer used descriptive comparative analysis. The writer compared a set of the English summative test content with a number of required items in the English syllabus content used in teaching and learning activities.The instruments were in the checklists forms which were arranged based on materials and objectives in syllabus of the 2013 Curriculum. The materials and objectives of each language skills were identified and arranged into the lists. They were changed into the questions as instrument. The research found that the content validity of the English summative test which was administered at the school was quite appropriate with the syllabus content of 2013 Curriculum. The percentage of the materials the material conformity was 20%. Meanwhile, the the percentage of objective reading skill conformity was 57%. And then, the the percentage of objective writing skill conformity was 64% However, in the listening and speaking skills could not be analyzed because they did not exist in the summative test for tenth grade student. The benefit of the research result is to help the teacher to arrange and make a good test.